The Influence of PJBL-based Student Worksheets on Improving Their Critical Thinking Ability and Digital Literacy - Heny Shofiyati; Rian Vebrianto; Mukti Amini (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper examines whether there is a difference in the results of the average scores of those who carry out learning using student worksheets based on the PJBL model and those who do not use student worksheets as well as comparing the efficiency between the use of student worksheets based on the PJBL model and the use of other methods on critical thinking skills and digital literacy in electrical circuit learning material at VI-grade students of SD Negeri 007 Sekip Hulu. This research is a quasi-experimental research using a post-test control group design. The study used a population of 44 students of class VI, which consists of 22 students in the experimental class (classVIa) who used PjBL-based worksheets, and 22 students in the control class (class VIb) who did not use the worksheets. Data were collected through tests and analyzed using the Paired Sample T-Test. The results indicate that the value of Sig.(2-tailed) 0.000 is less than 0.05, which implies that there is a significant average difference between the class that used PjBL-based Student Worksheets and the class that did not use PjBL-based Student Worksheets on critical thinking skills and digital literacy of students. In addition, the calculation of the N-Gain score test of the experimental class shows 81.0717 or 81.07% with the high and effective category. This value indicates that the use of PJBL-based Student Worksheets efficiently improves students' critical thinking skills and digital literacy in learning at class VI SD Negeri 007 Sekip Hulu in electrical circuit learning material. The conclusion shows that the use of PjBL-based LKPD can improve students’ critical thinking skills and digital literacy. The recommendation from the findings conducted by the researcher is that teachers can use PJBL-based LKPD for learning in class or other subjects so that students can be motivated to participate.